Exposure of CSR Dimension for Business Development: Case Study in Industrial Estate - Sarjana, Sri; Khayati, Nur; Warini, Lis; Praswiyati, Praswiyati (Universitas Negeri Semarang, 2020)
This study aims to find out how contribution of companies in industrial estate has an active involvement in corporate social responsibility (CSR) programs. In addition, the study also encourages companies to develop business in industrial estates, especially for industrial manufacturers in various business backgrounds through strengthening of the company’s active involvement in corporate social responsibility programs. Research has been conducted data collection and testing for the management in industrial estate at West Java, Indonesia. The sample selection was collected by using random sampling. Observations were made in time horizon or cross-sectional. Data were tested using structural equation modeling. The results concluded that the company has not been optimally involved in corporate social responsibility program. This can be seen from the lack of corporate contribution related to the role of company to engage directly on corporate social responsibility that can be felt and utilized by surrounding community to develop resources around it. The research expects for manufacturing industries in industrial estates to increase active involvement in corporate social responsibility programs as they positively impact business development in the future.